Performance comparison between skyhook and semi active damping force estimator (SADE) algorithms for semi active suspension system / S. A. Abu Bakar ... [et al.] - Abu Bakar, S. A.; Abdul Majid, M. M.; Mansor, S.; Abdul Hamid, M.K.; Daud, Z.C. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
An investigation on the performance of algorithms in semi active suspension system using a quarter car model has been performed. A Magnetorheological damper model has been developed and used as an actuator in the semi active suspension system. The Skyhook and Semi Active Damping Force Estimator (SADE) algorithms are used to control the operation of the MR damper in quarter car model’s suspension system. The damping coefficient value for both of the algorithms are intended to use the same value, for a fair untuned comparison in investigating the algorithm’s advantages in improving ride comfort performance of a quarter car model. The simulation model is subjected to a random road profiles with its amplitudes are ranging from -7.5 cm to 7.5 cm. The model’s vertical motions (vertical jerk, acceleration and, displacement, suspension working space and tyre dynamic loads) are observed in this studies. The mentioned responses are studied in both time domain and frequency domain results. It was found that the overall performance of untuned SADE-controlled semi active suspension system are at 52.1 percent, compared to the performance of the Skyhook semi active suspension system, which is at 58.1 percent. The use of SADE algorithm however ensures a small trade-off of suspension working space and tyre dynamic load when compared to the passive and Skyhook semi active suspension system.